Hak Guna Bangunan Untuk Investasi dalam Bidang Pariwisata - Larashati, Ida Ayu Putu (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
The role of the National Land Law in development is not yet perfect, but in reality the National Land Law has also succeeded in supporting development activities in all fields in the supply and management or utilization of the required land and legal certainty in its control and management or use. This study aims to examine building rights for investment in tourism. The method used is a normative research method due to legal uncertainty in the regulation of building rights as a form of tourism investment. The development of the tourism industry has an impact on various aspects of people's lives, both from the planned tourism industry and the unplanned implementation of the tourism industry.The impact of the planned implementation of the tourism industry development can be optimally anticipated. The principles of carrying out investments by using building rights as the basis for their rights can help the development of tourism because the holders of land titles do not lose ownership of their land. The structuring of sustainable tourism development is a development that has economic, socio-cultural and environmental dimensions so that it has justice not only for future generations. In this construction, tourism must be seen as a system that includes various components that interact with and influence each other. Therefore, it is needed a synergy of policies governing the implementation of tourism with a multisectoral and multidisciplinary approach to service integration, and the synergy of the government and the community in the use of land with Building Use Rights for tourism purposes